Legal Consequences of Bankruptcy on Joint Assets after Divorce - Putu Eka Trisna Dewi (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
Marriage is a legal event that makes a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the one and only God. However, not all marriages go as expected which leads to divorce. Marriage creates a union of assets called joint property. In the process of marriage, there are often a number of debts that the husband and wife cannot afford to pay because their joint assets are insufficient to pay these debts. The inability of a husband and wife to pay debts to creditors can be declared bankrupt based on a court decision. This will lead to a problem for joint assets when bankruptcy occurs after a divorce. This study aims to examine the legal consequences of bankruptcy on joint assets after divorce. The type of research is normative legal research. This legal research method is related to the principles and norms of bankruptcy law in Indonesia, in that, legal research is a process to find legal rules to answer the legal issues being faced. The types of approaches used are the statute approach, conceptual approach and legal facts approach. The results of this study showed that in Article 23 of the Bankruptcy Law, it is explained that if a person is declared bankrupt, those who participate in bankruptcy include the wife or husband with the status that the wife/husband after marriage is related to the union of assets. The legal consequences of the bankruptcy of joint assets that have not been divided after the divorce refer to the provisions for the distribution of joint assets in the marriage law and the Civil Code.